Diversity may help the uninterested: Evidence that exposure to counter-stereotypes promotes cognitive reflection for people low (but not high) in need for cognition. (December 2019) - Damer, Ekaterina; Webb, Thomas L.; Crisp, Richard J.
Previous theorizing and research has linked exposure to counter-stereotypical diversity (e.g., an Oxford-educated bricklayer) to enhanced cognitive performance and creativity. However, it is unclear whether people's motivation to cognitively engage with the counter-stereotypical information (i.e., need for cognition [NFC]) influences this effect. Across three experiments ( N = 887) we found consistent support for the idea that exposure to counter-stereotypes (CSTs) promotes cognitive reflection for people low in NFC ( d + = .34). In contrast, people high in NFC showed decreased cognitive reflection after being exposed to CSTs ( d + = −.18), although the evidence for the latter effect was weak. These findings suggest that exposure to CSTs can promote cognitive reflection unless people have a strong desire to understand and predict outcomes and events, in which case exposure to CSTs may backfire. Taken together, we conclude that motivation to engage in cognitive activity may be an important consideration for research and interventions involving social and cultural diversity.